The golden gate bridge barrier is completed - Mel Blaustein; A Bedrock (Annals of Psychiatry and Treatment - Peertechz Publications, 2023)
The Golden Gate Bridge will finally erect a barrier at the end of this year. The death toll since its completion in 1937 is about 2000. Two a month still jump to their deaths. The bridge is tragically known as the number one suicide site in the world.